A warmer way to do business Customer-driven business model innovation in the Swedish district heating industry - Broberg, Adam; Karlsson, Gustav (My University, 2025)
District heating currently supplies over 60 % of Sweden’s total heating demand, making it a cornerstone of the country’s energy system. Despite this central role, district heating companies face increasing customer scrutiny due to rising prices, evolving expectations, and growing competition from competing technologies, mainly heat pumps. Historically, the sector’s natural monopoly characteristics have shielded it from competitive pressures, and its extensive municipal ownership has contributed to a limited focus on market positioning and customer perception. However, as scrutiny intensifies, there is an urgent need to reconsider how district heating companies operate, structure their business models, and engage with their customers. This research investigated strategic business model innovation opportunities for district heating companies in response to these challenges. The research was carried out in collaboration with Norrenergi AB, a district heating and cooling company in the Stockholm region. The research applied an outside-in perspective, drawing on insights from interviews with customers, industry professionals, and experts to incorporate viewpoints beyond solely internal perspectives. The findings indicate that the current value offering in the district heating industry is undifferentiated and therefore often fails to adequately meet the diverse needs that customer segments seek to fulfill when purchasing an energy solution. Additionally, concerns were raised about the industry’s pricing structure, a lack of customer focus and engagement, and a perceived slowness in adapting to evolving customer expectations. The report recommends that district heating companies move beyond traditional segmentation schemes and adopt a jobs-to-be-done approach. This shift would enable the creation of more tailored value propositions for distinct customer profiles and guide the development of aligned value creation, delivery, and capture components. For theory, the report contributes with a systematic, outside-in approach to business model innovation, operationalized through a conceptual lens that follows a phased process based on the 4I methodology and integrates the jobs-to-be-done framework and business model patterns.
Keywords: Energy; District heating; District Cooling; Business model innovation; Business model patterns; Customer-driven innovation; Jobs-to-be-done